On the Origins and Persistence of the Jewish Identity Industry in Jewish Education. Issue 2 (2nd April 2016) - Krasner, Jonathan
ABSTRACT: "Jewish identity, " which emerged as an analytical term in the 1950s, appealed to a set of needs that American Jews felt in the postwar period, which accounted for its popularity. Identity was the quintessential conundrum for a community on the threshold of acceptance. The work of Kurt Lewin, Erik Erikson, Will Herberg, Marshall Sklare, and others helped to shape the communal conversation. The reframing of that discourse from one that was essentially psychosocial and therapeutic to one that was sociological and survivalist reflected the community's growing sense of physical and socioeconomic security in the 1950s and early 1960s. The American Jewish Committee and its Division of Scientific Research offers an enlightening case study of this phenomenon. Jewish educators seized on identity formation, making it the raison d'être of their endeavor. But the ascent of identity discourse also introduced a number of challenges for the Jewish educator—conceptual, methodological, political, and even existential.